FEASIBILITY STUDY THE GANGSA UBUD PRIVATE VILLA & SPA DI DESA PAYOGAN, KECAMATAN UBUD, KABUPATEN GIANYAR - Suyanto Sindudarmo, The; Sedana, I B Panji (E-Jurnal Ekonomi dan Bisnis Universitas Udayana, 2018)
The tourism sector is one of the important sources of state revenue. The arrival’s number of foreign tourist to Bali is increasing both of quantity and quality, therefore the improvement of tourism facilities is needed. One of the example is  providing good  accommodation (rooms) in accordance with the needs and expectations of guests, but to provide accommodation services through the development of a lodging should give attention to aspects of the feasibility study. The results of this feasibility study will show the project / investment is feasible or not feasible. This research was conducted in Payogan village, Ubud district, Gianyar regency, Bali, which is the investment / construction project of The Gangsa Ubud Private Villa & Spa located. Data analysis methods used are more focused on the analysis of market and marketing aspects, and analysis of financial aspects. Research result indicates that business idea for gangsa Ubud Private Villa & Spa is feasible based on market and marketing aspects and financial aspects.